Study of a Natural Mutant SHV-Type β-Lactamase, SHV-104, from Klebsiella pneumoniae - Nahed Ben Achour; Omrane Belhadj; Moreno Galleni; Mohamed Ben Moussa; Paola Sandra Mercuri (International Journal of Microbiology)
Klebsiella pneumoniae ML2011, a multiresistant isolate, was isolated from the Military Hospital of Tunis (Tunisia). The determination of the minimal inhibitory concentrations exhibited by K. pneumoniae ML2011 was performed by Etest. The crude extract of the isolates contains four different β-lactamases with pI 5.5, 7.3, 7.6, and 8.6. Only the β-lactamases with pI 7.3 and pI 8.6 were transferred by transformation and conjugation experiment. Molecular characterization of these genes was performed by PCR and sequencing. The chromosomal β-lactamases are TEM (pI 5.5) and SHV-1 (7.6). CTX-M-28 (pI 8.6) and the novel variant of SHV named SHV-104 (pI 7.3) were encoded by bla gene located on a 50 kb highly conjugative plasmid. The SHV-104 β-lactamase was produced in E. coli and purified. Its profile of activity was determined. Compared to SHV-1, SHV-104 contains one mutation, R202S. Their kinetic parameters were similar except for cefotaxime. The analysis of the predicted structure of SHV-104 indicated that the R202S mutation suppresses a salt bridge present in SHV-1. Therefore, the overall flexibility of the protein increased and might improve the hydrolysis of cefotaxime. We can conclude that the multiresistant phenotype of K. pneumoniae ML2011 strain is mainly linked to the production of CTX-M-28 since SHV-104 possesses a narrow spectrum of activity.